Report 4: The Dissemination Potential of a European Network - Looy, Anne de (2011)
The report that follows represents an extraordinary and unique exchange of information. Unfolding here are the capabilities for dissemination and exploitation in the EU-funded Thematic Network ‘Dietitians Implementing Education and Training Standards’ in Europe (DIETS). At the beginning of the Network there were 112 Partners and about 500 registered users of the DIETS website, but over a three-year period this has increased to 123 Partners and well over 1000 users. The activity of these Partners and their determination to publicise the Network and, more importantly, the role of the dietitian, has been immense and sometimes difficult to capture. However, captured in this report are the learning and change to practice that has resulted, as well as closer engagement between HEIs and their dietetic departments across Europe. Some of the good practice described here will be of value to others starting this type of journey. This network of HEIs, their dietetic colleagues and others will endure long after the DIETS Network has finished its work, largely due to the enthusiasm of the Partners and the social network that has been built and embedded. The ultimate benefit to dietitians, through education, lifelong learning and their contribution to nutritional health in Europe will continue to unfold.